2020
DOI: 10.1007/s10508-019-01620-x
|View full text |Cite
|
Sign up to set email alerts
|

PrEP Interest Among Men Who Have Sex with Men in the Netherlands: Covariates and Differences Across Samples

Abstract: Despite increased availability of pre-exposure prophylaxis (PrEP), PrEP uptake has remained low. To promote uptake, factors related to PrEP interest among relevant target populations warrant investigation. The aim of this study was to provide an analysis of PrEP interest among men who have sex with men (MSM) in the Netherlands, while taking study recruitment strategies into account. We recruited 154 MSM from an LGBT research panel (AmsterdamPinkPanel) and 272 MSM from convenience sampling. Both samples were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…As a biomedical intervention and part of comprehensive prevention measures, pre-exposure prophylaxis (PrEP) is highly effective in preventing HIV-negative MSM from acquiring HIV [ 2 , 3 , 4 , 5 , 6 ]. In response, PrEP was formally introduced in Europe in 2016 and was subsequently included in the Dutch national delivery plan in September 2019 through the sexual health clinics of the Public Health Services (GGD) [ 1 , 7 , 8 , 9 ]. It is estimated that around 10,000 MSM meet the eligibility criteria for PrEP in the Netherlands [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a biomedical intervention and part of comprehensive prevention measures, pre-exposure prophylaxis (PrEP) is highly effective in preventing HIV-negative MSM from acquiring HIV [ 2 , 3 , 4 , 5 , 6 ]. In response, PrEP was formally introduced in Europe in 2016 and was subsequently included in the Dutch national delivery plan in September 2019 through the sexual health clinics of the Public Health Services (GGD) [ 1 , 7 , 8 , 9 ]. It is estimated that around 10,000 MSM meet the eligibility criteria for PrEP in the Netherlands [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, PrEP intention among MSM data have been mostly gathered among MSM residing in Amsterdam [ 7 , 13 , 14 , 15 ]. Cross-sectional data from these Amsterdam-based studies revealed that PrEP intention among MSM increased from 13% (high intention to use) during the initial assessment in 2013 [ 13 ] to a higher proportion of definite intention of almost 40% in 2016 [ 7 ]. To corroborate these findings, a significant increasing trend of informal PrEP uptake among Dutch MSM residing in Amsterdam from 2015 to 2017 was also observed [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study in London reported that compared with older MSM, MSM who were younger were more likely to consider future PrEP use (Aghaizu et al, 2013). Having multiple sex partners or being at a higher risk of HIV/STI acquisition was also suggested as contributory attributes to finding PrEP favorable (Bil et al, 2015;Van Dijk et al, 2020). The context of dating apps in allowing prompt sexual encounters among MSM with different profiles and the rise of PrEP as a biomedical HIV prevention option compound the already complicated struggle against the use of substances during sex among MSM (Kwan & Lee, 2019;Maxwell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%